Humanization of Education in the Challenges and Opportunities of the Disruption Era at Nahdlatul Ulama Elementary School - Ahmad Tarmizi Hasibuan; Nurzakiah Simangunsong; Ely Rahmawati; Rahmaini Rahmaini (IAIN Syekh Nurjati Cirebon, 2020)
AbstractThis study was intended to describe the concept of humanization of education which is implemented at the Nahdlatul Ulama Elementary School (SD NU) Sleman Yogyakarta in facing challenges and opportunities in the era of disruption. This type of research is qualitative in the form of a phenomenological approach. In collecting data, researchers used observation, interview, and documentation techniques. Meanwhile, the research data were analyzed using Miles and Huberman model and validated through data triangulation techniques. The results showed that in implementing humanist education at SD NU Sleman Yogyakarta, the school used Sab'atu Ansitoh (7M) activities. They are first, cultivating and instilling behavior; second, grounding the NU pledge of allegiance; third, practice riyadhoh; fourth, improving school facilities; fifth, training educators; sixth, making educators prosperous; and seventh, providing a child-friendly canteen (iqomatil maqsof). It is expected that applying these 7 principles (sab'atu ansitoh) can have implications for improving the quality of students who are able to face the challenges in the era of disruption.Keywords: disruption era, humanization of education, Nadlatul Ulama elementary school. AbstrakPenelitian ini bertujuan untuk mendeskripsikan konsep humanisasi pendidikan yang diimplementasikan di Sekolah Dasar Nahdlatul Ulama (SD NU) Sleman Yogyakarta dalam menghadapi tantangan dan peluang di era disrupsi. Jenis penelitiannya adalah kualitatif dengan pendekatan fenomenologis. Dalam pengumpulan data, peneliti menggunakan teknik observasi, wawancara, dan dokumentasi. Sementara itu, data hasil penelitian dianalisis menggunakan analisis data model Miles dan Huberman dan uji keabsahan data menggunakan teknik triangulasi data. Hasil penelitian menunjukkan bahwa dalam mengimplementasikan pendidikan yang humanis di SD NU Sleman Yogyakarta, pihak sekolah menggunakan kegiatan Sab’atu Ansitoh (7M), yaitu pertama, membudayakan dan menanamkan adab; kedua, membumikan Ikrar kesetiaan NU; ketiga, mentradisikan riyadhoh; keempat memajukan fasilitas sekolah; kelima, melatih pendidik; keenam, mensejehterakan pendidik; dan ketujuh, menyediakan kantin (iqomatil maqsof) ramah anak. Diharapkan dengan menerapkan 7 prinsip (sab’atu ansitoh) tersebut dapat berimplikasi terhadap peningkatan kualitas siswa yang mampu menghadapi tantangan di era disrupsi.Kata kunci: era disrupsi, humanisasi pendidikan, Sekolah Dasar Nahdlatul Ulama.